2019
DOI: 10.1002/fsn3.1286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enzyme‐assisted hydrolysis on protein pattern, technofunctional, and sensory properties of lupin protein isolates using enzyme combinations

Abstract: The modification of lupin protein isolates (LPI) by means of enzymatic hydrolysis ( Lupinus angustifolius cultivar Boregine) was performed with four enzyme preparations (Alcalase 2.4 L, Papain, Corolase 7089, and Neutrase 0.8 L) in a one‐ and two‐step process to determine the efficacy for the destruction of major IgE‐reactive polypeptides and the evaluation of the technofunctional and sensory properties of lupin protein hydrolysates. Combinations of Alcalase 2.4 L and Papain were most ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…The 10% hydrolysate was the best concentration in terms of nutritional parameters and sensory scores [735], later this product was remarked as a functional food [736]. Corolase, papain, Alcalase and Neutrase were individually used or in a two-step process to hydrolyze lupin (Lupinus angustifolius cultivar Boregine) protein isolates [737].…”
Section: Combined Use Of Alcalase With Other Proteasesmentioning
confidence: 99%
“…The 10% hydrolysate was the best concentration in terms of nutritional parameters and sensory scores [735], later this product was remarked as a functional food [736]. Corolase, papain, Alcalase and Neutrase were individually used or in a two-step process to hydrolyze lupin (Lupinus angustifolius cultivar Boregine) protein isolates [737].…”
Section: Combined Use Of Alcalase With Other Proteasesmentioning
confidence: 99%
“…Alcalase 2.4 L hydrolysates are known for bitter taste. Several studies have already shown that the hydrolysis of plant proteins such as lupin [ 7 , 10 ], soy [ 6 ] and pea [ 27 ] results in a bitter taste. However, S4 ( Lactobacillus sakei ssp .…”
Section: Resultsmentioning
confidence: 99%
“…Unfermented LPI (−0.896/−1.108) was in close correlation with the pea-like aroma attribute and was found on the negative side of PC2, together with the Papain hydrolysates samples S1 (Lactobacillus sakei ssp. carnosus) and S3 (Lactobacillus helveticus) and the Alcalase 2.4 L hydrolysates samples S5 (Lactobacil- [7,10], soy [6] and pea [27] results in a bitter taste. However, S4 (Lactobacillus sakei ssp.…”
Section: Sensory Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Zang et al explained that the release of soluble peptides from insoluble aggregates or precipitates, and an increased number of exposed ionizable amino and carboxyl groups, were the reasons behind the increased protein solubility and DH [153]. Schlegel et al reported that lupin protein hydrolysates showed a significant increase in foaming activity, as compared to the native sample [156]. The increase in foaming activity was a result of the change in protein structure, which exposed the hydrophilic and polar groups to interactions with an aqueous environment.…”
Section: Biological Modificationsmentioning
confidence: 99%